NEW TECHNOLOGIES IN DIAGNOSIS OF PRIMARY OPEN-ANGLE GLAUCOMA - N.I. KURYSHEVA (International Journal of Pharma and Bio Sciences, 2016)
The purpose of the study is to determine the most important diagnostic criteria for distinguishing preperimetric glaucoma from perimetric glaucoma on the basis of a comprehensive assessment of structural changes and indicators of ocular blood flow. 90 eyes, including 30 eyes with preperimetric glaucoma, 30 eyes with perimetric glaucoma, and 30 normal eyes were analyzed in the present study. The average thickness of the ganglion cell complex (avgGCC), retinal nerve fiber layer (RNFL) and choroidal thickness (CT) were measured using RTVue-100 spectral-domain optical coherence tomography (SD-OCT). Standard automated perimetry (SAP) was performed on Humphrey perimeter (Carl Zeiss Meditec, Dublin, CA). Ocular blood flow parameters were measured by color Doppler imaging (CDI) and pulsed-wave Doppler (PWD). Corneal compensated intraocular pressure (IOPcc) and corneal hysteresis (CH) were determined using Ocular Response Analyzer (ORA). Perfusion pressure (PP) was studied by means of measuring intraocular pressure (IOP) and arterial blood pressure (BP) immediately before OCT scanning. As a measure of the parameter importance in distinguishing groups, a value of the adjusted standardized statistic of the Mann-Whitney test (z-value) and the area under the receiver operating characteristic (ROC) curve (AUC) were applied. The result shows that the difference between perimetric and preperimetric glaucoma could be characterized by 4 important diagnostic criteria: RNFL (AUC 0.93; z-value 5.75), peripapillary choroidal thickness, or pCT (0.7; 2.69), the end-diastolic blood flow velocity in the nasal short posterior ciliary arteries (0.7; 2.55) and CH (0.68; 2.41). In conclusion, RNFL, pCT, CH and the end-diastolic blood flow velocity in the nasal short posterior ciliary arteries are the most important parameters in distinguishing preperimetric glaucoma from perimetric glaucoma; and that should be considered when monitoring the disease.